Aportaciones a la flora de Andalucía. II. - Cabezudo, Baltasar; Pérez Latorre, Andrés V.; Navas, David; Caballero, Gonzalo; Gavira, Óscar (Acta Botanica Malacitana, 2003)
New data on the Andalusian flora. II. Palabras clave. Juniperus, Dryopteris, Moehringia, Ulex, Fran gula, Lithodora, Atropa, flora, corología, Andalucía, España. Key words. Juniperus, Dryopteris, Moehringia, Ulex, Fran gula, Lithodora, Atropa, flora, chorology, Andalusia, Spain.